Upaya Dinas Pariwisata Ternate Dalam Mengatasi Penurunan Kunjungan Wisatawan Di Daya Tarik Wisata Pantai Sulamadaha - Ayu Astrid Fabanyo; I Gede Anom Sastrawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
This study aims to determine the factors that cause a decrease in tourist visits and efforts made by the Ternate City Tourism Office in overcoming the decreasing intensity of tourist visits in Sulamadaha Beach Tourism Attractions. Ternate located in North Maluku Province. Ternate is one of 10 districts in North Maluku Province that have many tourist attractions, for example Sulamadaha Beach. Sulamadaha Beach is an attraction that is managed directly by the Ternate City Tourism Office and the local community, Sulamadaha Beach has beautiful underwater natural beauty, according to data from the Ternate City Tourism Office Sulamadaha Beach is the most popular destination for tourists, but this does not last long as it is known from the data of tourist visits that Sulamadaha Beach every year has decreased, related to this, it will be research about